Enhancing EFL Students’ Speaking Ability through a HOTS based Show and Tell Technique - Alfiana Alfiana; Nurhamdah Nurhamdah; Magdahalena Tjalla; Muh. Yusuf (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigated the effectiveness of a HOTS-Based Show and Tell technique in enhancing EFL students’ speaking ability. The study employed a quantitative approach using a pre-experimental one-group pre-test and post-test design. The participants were 36 eleventh-grade students of SMAN 2 Parepare. Data were collected through speaking tests and analyzed using descriptive statistics and a paired-samples t-test. In the implementation of the technique, students were encouraged not only to describe objects or topics but also to analyze, evaluate, and express personal opinions, thereby incorporating Higher Order Thinking Skills (HOTS) into speaking activities. These tasks required students to explain reasons, compare ideas, solve simple problems, and support their arguments during presentations. The findings revealed that students’ speaking ability improved significantly after the implementation of the technique. The mean score increased from 36.44 in the pre-test to 55.67 in the post-test, with a significance value of p .001. The results indicate that integrating HOTS into Show and Tell activities can promote more meaningful speaking practice, increase student participation, and create a more interactive learning environment in EFL classrooms.